eq_sheet(2) - s = + j dN y dN 1 y dy + a1 N 1 + + aN 1 + aN...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
s = σ + d N y dt N + a 1 d N - 1 y dt N - 1 + ··· + a N - 1 dy dt + a N y ( t ) = b N - M d M x dt M + b N - M +1 d M - 1 x dt M - 1 + ··· + b N - 1 dx dt + b N x ( t ) y [ n ] + a 1 y [ n - 1] + ··· + a N - 1 y [ n - N + 1] + a N y [ n - N ] = b 0 x [ n ] + b 1 x [ n - 1] + ··· + b N - 1 x [ n - N + 1] + b N x [ n - N ] X ( s ) = Z -∞ x ( t ) e - st dt | H ( s ) | s = p = b 0 product of distances of zeros to p product of distances of poles to p 6 H ( s ) | s = p = sum of zero angles to p - sum of pole angles to p X [ z ] = X n = -∞
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 12/14/2011 for the course BME 343 taught by Professor Emelianov during the Spring '09 term at University of Texas at Austin.

Ask a homework question - tutors are online